Surgical removal of peripheral nerve schwannoma with intraoperative neurophysiological monitoring - Prakash Chandragouda Bharamagoudar; Shivashankar Marajakke (Journal of the Scientific Society, 2019)
Schwannomas are the most common peripheral nerve tumors arising from neural sheath. They account for <8% of soft-tissue neoplasm. Surgical excision is the only option when patients present with complaints such as paresis, palsy, paresthesia, and pain. The essential goal of surgery will be complete excision of tumor with preserving nerve function. Intraoperative neurophysiological monitoring (INM) gives basic, reliable, and real-time information on the functionality of explored nerve, which helps the surgical team in microscopic dissection of tumor and complete removal without damaging the normal nerve fasciculi. We present a case of complete surgical excision of radial nerve schwannoma in a 48-year-old male, with INM and without any postoperative neurodeficits.